Clinico-pathological Evaluation of Aspiration Pneumonia in Cattle - Kaliappan, Sasikala; Elumalai, Venkatesakumar; Subramanian, Sivaraman; Ramasamy, Ravi; Premkumar, Ramkumar; Shanmugam, Kathirvel (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Aspiration pneumonia is an essential and frequent complication following aspiration of abnormal substances in the airways and alveoli.  The objective of this study was to determine the clinical, haemato-biochemical, radiographic, and post-mortem changes and therapeutic  management of cattle with aspiration pneumonia. Six Jersey crossbred and four Holstein Friesian crossbred cattle were reported with a  history of cough, respiratory distress, oral breathing, inappetence, and pyrexia for 2–5 days following faulty drenching and regurgitation  due to ruminal lactacidosis. Three animals were brought immediately after aspiration. Clinical examination revealed cough, extended  head and neck, bilateral mucopurulent nasal discharge, dyspnoea, polypnoea, pyrexia, and ozena. Exaggerated tracheal and lung  sounds, crackles, wheezes, and pleuretic frictional sounds were noticed on auscultation. Leukocytosis with neutrophilia was noticed  on hematological examination. Lateral thoracic radiographs showed pulmonary infiltrates, indicating aspiration pneumonia. Animals  were parenterally administered with ceftiofur sodium, flunixin meglumine, and nebulization with ceftiofur sodium and budesonide.  Therapeutic outcomes were discussed in detail in this article.
Keywords: Aspiration; Crossbred cattle; Drenching; Pneumonia; Therapy